An integrated simulation modelling framework for decision aids in enterprise software development process. (26th May 2009) - Lee, Seungho; Celik, Nurcin; Son, Young-Jun
Development of enterprise software systems requires the collaboration of many stakeholders that form a complex social network. The goal of this paper is to propose a novel simulation modelling framework, which will allow the stakeholders to perform what-if analyses before making their decisions. The proposed framework involves four different modelling paradigms, including Bayesian belief network, Belief-Desire-Intention mimicking a human decision, game-theory mimicking interactions of humans with conflicting goals, and system dynamics for an overall software development. The proposed framework is illustrated with a real case study in Kuali, which is an open source project currently under development by nine universities.